PENGADAAN BAHAN BAKU DAN HARGA POKOK PRODUKSI PADA INDUSTRI RUMAH TANGGA KERUPUK LIA JAYA DI DESA PASAR PEDATI KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Sahputra, Royi; Fariadi, Herri; Andriani, Evi (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Lia Jaya home industry produces seven types of crackers: tofu, firecracker sticks, jalin, tempeh, macaroni, jengkol, and fish crackers. Procurement and costs that are not small must be incurred during its business activities. In calculating the cost of production, these costs are very important components to be studied. The purpose of this study was to determine the Cost of Production (HPP) of the Lia Jaya Cracker home industry in Pasar Pedati Village, Pondok Kelapa District, Central Bengkulu Regency and to determine the sources of raw materials used by the company. This study was conducted through a quantitative descriptive approach involving analysis of the cost of production and analysis of raw material procurement. The results of the study showed that the raw materials for making Lia Jaya crackers were purchased from Banyuwangi, East Java, and sent once a month. The amount of raw materials usually ordered is 6,740 kilograms per month. In May 2024, the Lia Jaya cracker household business produced 7 products, with a production cost of IDR 185,001,462/month. The production cost of macaroni is 24,521,562 per month or 28,849 per kilogram, and jengkol crackers are 23,223,362 per month or 23,223,362 per kilogram. The price of firecracker sticks is 22,681,331 per month or 27,327 per kilogram, Jalin crackers are 23,375,536 per month or 27,181 per kilogram, and tempeh crackers are 21,933,987 per month or 27,417 per kilogram.